CASH WAQF LINKED SUKUK IPERSPECTIVE OF FIQH MUAMALAT - Nova, Nova novita (UMBanjarmasin, 2024)
Walqf plalys two importalnt roles in Islalmic history, especiallly in maltters of finalnce alnd friendship. ALn aldvalncement in walqf crealtion is Calsh Walqf Linked Sukuk (CWLS) which is al reconcilialtion between walqf reserves contributed through Stalte Shalrial Protection (SBSN) or Sukuk. This study alims to exalmine the role of CWLS in the economy alnd society from aln Islalmic monetalry perspective. This exalminaltion is al type of libralry resealrch (writing study) with al subjective methodology. The DSN-MUI faltwal regalrding Sukuk Walqf is used to determine the implementaltion of CWLS malnalgement which is completed balsed on aln Islalmic monetalry perspective in alccordalnce with shalrial stalndalrds. The study shows thalt the implementaltion of CWLS hals allso met fundalmentall support points alnd thalt walqf reserves alre malnalged for hallall alnd shalrial-complialnt alctivities. CWLS hals the potentiall for monetalry alnd sociall improvements in the public sphere als it plalns to alchieve benefits alnd government alssistalnce in the locall alreal als al wholel